2014
DOI: 10.1111/josh.12193
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analyses of School and Children's Characteristics Associated With Physical Activity

Abstract: School environment is an important correlate of PA among children, enhancing children's opportunities for being active and healthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
18
0
3
Order By: Relevance
“…First, we assessed the degree of clustering, or the proportion of variance attributable to the school level, by calculating intraclass correlation coefficients (ICCs) for each PA outcome. Next, using methods employed in previous school-based research (8,9) and recommendations from other researchers (16), we constructed models in a series of steps to assess model fit, separately for boys and girls, controlling for age and BMI z score as potential confounders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we assessed the degree of clustering, or the proportion of variance attributable to the school level, by calculating intraclass correlation coefficients (ICCs) for each PA outcome. Next, using methods employed in previous school-based research (8,9) and recommendations from other researchers (16), we constructed models in a series of steps to assess model fit, separately for boys and girls, controlling for age and BMI z score as potential confounders.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies, however, operationalize the neighborhood as the area surrounding the home and thus may not be useful in informing policy to support PA around schools. Moreover, children’s PA behaviors often vary considerably from school to school (8,9), especially in NYC (10), potentially resulting from characteristics of the neighborhood’s built environment.…”
Section: Introductionmentioning
confidence: 99%
“…A school environment that promotes play has the potential to contribute to young people attaining the recommended amounts of daily physical activity. 16 Several studies have found that interventions based on playground markings and physical structures increase the physical activity of children during recess, 17 and a larger number of outdoor facilities is associated with students being more physically active during school breaks 18 and overall 19 compared with students in schools with fewer facilities. In contrast, one systematic review reported that there was inconclusive evidence for positive effects of playground interventions in the school setting on children's physical activity levels.…”
mentioning
confidence: 98%
“…Godin leisure-time exercise questionnaire: It is a simple and feasible self-report instrument which is valid and reliable PA measure [43,44]. Children were asked about the number of times/week that they spent in different activities for a period at least 15 minutes.…”
Section: Measures For Physical Activitymentioning
confidence: 99%